PERANAN FUNGSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN SD NEGERI 129 WAEMPUBBU - Sulistiawati, Eka; Hasbi, M; Satriani, Satriani; A, Arisal (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2022)
Futyour: People are starting to know that having a quqlity education can make progres. In education institutions, the principal is an important of the school committe structure, ranging from primary to secondary education in fact,as the principal, has many oligations, authorities,responsibilitties, and funcitions. The high demand from society for education causes the need for schools with quality educational services, and the existence of school in the community is becoming increasingly needed The success or failure of a service in achieving its goals depends on its consumer, in the sense that institutional institutions need to provide quality services to users of educational services in order to achieve their goals. However, there are still shose who not integrated it properly.This study aims to determine the managerial function of the principal at SDN 129 Waempubbu, to determine the quality of education service at SDN 129 Waempubbu, and to determine the role of the principal’s managerial function improving the quality of educatio services at SDN 129 Waempubbu. The research method used was qualitative research. The results of this study indicate that SDN 129 Waempubbu has implemented the role of the principal’s managerial funcition optimally and the quality of education services still needs to be improved in the future.